2011
DOI: 10.1007/s12033-011-9409-3
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Glycated Proteins from Streptozotocin-Induced Diabetic Rat Kidney

Abstract: Glycation of proteins leading to formation of advanced glycation end products (AGEs) has been considered as one of the important causes of diabetic nephropathy. Therefore, in this study, glycated proteins were detected by anti-AGE antibodies from kidney of streptozotocin-induced diabetic rat showing nephropathic symptoms, by using two dimensional electrophoresis and western blot analysis. These glycated proteins were identified and characterized by using combination of peptide mass finger printing and tandem m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…The experiment was repeated independently three times. modified by various glycation modifications, common to our previous study (12). Hence, these results provided additional evidence that the protease resistance of these proteins is caused by a variety of AGE modifications.…”
Section: Fig 4 Validation Of Lc-mssupporting
confidence: 84%
See 2 more Smart Citations
“…The experiment was repeated independently three times. modified by various glycation modifications, common to our previous study (12). Hence, these results provided additional evidence that the protease resistance of these proteins is caused by a variety of AGE modifications.…”
Section: Fig 4 Validation Of Lc-mssupporting
confidence: 84%
“…Proteins of extracellular matrix, kidney, as well as proteins from circulation, get AGE modified and trapped in the kidney (12). Both intracellular and extracellular AGEs have been observed in the diabetic kidney.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…abundant plasma protein (22) and preferentially gets glycated (23). Amadori-modified albumin is reported to be independently associated with nephropathy in type 1 diabetic patients (24), and in our previous study, AGE-modified serum albumin was detected in the kidney of STZ-induced diabetic rats (25). Glycated albumin levels are reported to be elevated significantly in type 2 diabetic patients with coronary artery disease (26).…”
Section: Elevated Human Serum Albumin In Cics Of Plasma From Prediabementioning
confidence: 77%
“…Very recently, iTRAQ based proteomic studies from IGIB, New Delhi have shown that downregulation of apolipoproteins and albumin might be responsible for impaired reverse cholesterol transport in stable CAD [76]. Interesting findings in Type 2 diabetes have emerged from proteomic studies carried out at NCL, Pune in human plasma and drug induced animal models [7785]. One of the novel initiatives undertaken by this group is to study advanced glycation end products (AGE) in a diabetic animal model using MALDI–TOF–MS based proteomics [82].…”
Section: Reviewmentioning
confidence: 99%